Three Swedish Missionaries: Images of Music in Southern Africa - Thorsén, Stig-Magnus (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2005)
The present Swedish perceptions of Africa are biased by an inherited view of African culture. Swedish missionaries have historically contributed to a narrative, disseminated through churches, schools, and mass media. The number of people involved with missions far exceeds the number of those in the other categories. Consequently, they have had a strong impact on the common understanding of music from Africa that I generally encounter in Sweden. My central question is: How have missionaries reflected music in Africa? Data is limited to the Church of Sweden’s mission in southern Africa 1875-1990. Written accounts form the basis of my research material, and are supplemented by interviews. In particlar, I will discuss Hedvig Posse, Henry Weman, and Olof Axelsson, leaders who represent three generations of missionaries. Each of them offered a different understanding of the image of music in Africa. Their written accounts from Africa are significant both in details and extent, focusing on the musical rather rather than its function. The indifference to musical functions has to a large extent underpinned false generalizations and stereotyping. Evidently, Posse and Weman knew too little about the relation between music and society in the environment in which they worked. Posse seems to have had a very loose relation even to Swedish music. In Weman’s perspective, any music of Africa indifferently became a neutral language or carrier of texts, and the esthetic judgement of the end-result was filtered through his Western “church-music ears.” Lacking was a deeper and specific knowledge of how music permeates and reflects societal changes.